It does matter where you come from: mothers' experiences of childbirth in midwife obstetric units, Tshwane, South Africa - Sarie J. Oosthuizen; Anne-Marie Bergh; Robert C. Pattinson; Jackie Grimbeek (BMC, 2017)
Abstract Background Health professionals are striving to improve respectful care for women, but they fall short in the domains of effective communication, respectful and dignified care and emotional support during labour. This study aimed to determine women's experiences of childbirth with a view to improving respectful clinical care practices in low-risk, midwife-led obstetric units in the Tshwane District Health District, South Africa. Methods A survey covering all midwife-led units in the district was conducted among 653 new mothers. An anonymous questionnaire was administered to mothers returning for a three-days-to-six-weeks postnatal follow-up visit. Mothers were asked about their experiences regarding communication, labour, clinical care and respectful care during confinement. An ANCOVA was performed to identify the socio-demographic variables that significantly predicted disrespectful care. Six items representing the different areas of experience were used in the analysis. Results Age, language, educational level and length of residence in the district were significantly associated with disrespectful care (p ≤ 0.01). Overall, the following groups of mothers reported more negative care experiences during labour: women between the ages of 17 and 24 years; women with limited formal education; and women from another province or a neighbouring country. Items which attracted fewer positive responses from participants were the following: 46% of mothers had been welcomed by name on arrival; 47% had been asked to give consent to a physical examination; and 39% had been offered food or water during labour. With regard to items related to respectful care, 54% of mothers indicated that all staff members had spoken courteously to them, 48% said they had been treated with a lot of respect, and 55% were completely satisfied with their treatment. Conclusion There is a need to improve respectful care through interventions that are integrated into routine care practices in labour wards. To stop the spiral of abusive obstetric care, the care provided should be culturally sensitive and should address equity for the most vulnerable and underserved groups. All levels of the health care system should employ respectful obstetric care practices, matched with support for midwives and improved clinical governance in maternity facilities.